Landscape evolution and hydrogeochemical characteristics of the Pourewa Stream catchment, lower North Island, New Zealand. Issue 2 (3rd April 2019) - Rees, Callum; Palmer, Julie; Palmer, Alan; Singh, Ranvir
ABSTRACT: Issues regarding water quality and supply have been raised within the Pourewa catchment, following ongoing landuse change and associated demand for freshwater. Nitrogen loss from farms due to leaching of nitrate into the subsurface has increased in conjunction with landuse intensification. The stream dissects Whanganui Basin fill, including alternating coarse and fine-grained sediments deposited throughout Quaternary climatic cycles, resulting in interbedded aquifers and aquitards in a geologically young landscape. The Rangitikei River dominates the landscape, forming a series of aggradational terraces. Fault lines and basement highs provide a control on both the underlying Plio-Pleistocene strata and modern-day drainage network. A 1:25 000 hydrogeological map and corresponding structural interpretation are presented. Analysis of catchment lithologies demonstrates the importance of grain size, porosity and age in dictating hydraulic conductivity. Organic carbon, illite and glauconite present within the succession indicate attenuation of nitrate within the local groundwater system is taking place.